Assessing the UK public's ability to identify trees using the analysis of photographic queries. Issue 1 (2nd January 2020) - Smith, Tim
ABSTRACT: Engagement with the natural world is a key aspect to its protection, and so knowing what species the public can identify is important in allocating often limited time and resources. This study examines a data-set of photographic identification that were sent to the Woodland Trust to be identified. The analysis found that deciduous rather than evergreen trees were most frequently queried, with Spring and Autumn the most active seasons for engagement. Individual genus and species were isolated from the data, more variable species appearing to be most often queried. Suggestions on how these data can be utilised are given, as well as its limitations.